Principles of legal proceedings in the Code of administrative proceedings and in the Civil procedure code - Lydia A. Terekhova (Правоприменение)
The subject. The system of principles of legal proceedings is one of the indicators of the independence of the type of legal proceedings. The article analyzes the general and distinctive features of the principles enshrined in the Russian Civil Procedure Сode and the Code of Administrative Procedure.The purpose of the article is confirmation or confutation of the hypothesis that there is no independent system of principles of administrative proceedings that differs from the system of principles of civil proceedings.The methodology of the study includes the formal legal method, analysis, synthesis.The main results. All of the principles enshrined in the Code of Administrative Procedure are also enshrined in the Civil Procedure Code except some minor characteristics. So, the active role of the court, involving a number of exceptions to the usual rules of evidence, was also characteristic of the regulation of the consideration of cases arising from public legal relations in the Code of Civil Procedure. The court’s active actions to determine the subject of evidence, to recover evidence are general rules of evidence for all types of proceedings. These rules existed both before the adoption of the Code of Administrative Procedure and after it. But the specifics of the execution of judicial acts adopted in cases of administrative proceedings require special attention. A characteristic feature in the consideration and resolution of most administrative cases is the immediate execution of decisions enshrined directly in the Code of Administrative Procedure. Such a rule can be considered as a priority of immediate execution, which is a characteristic feature of administrative proceedings. The author doubts about the need for normative consolidation of the principles, as well as the need for a special list of principles of administrative legal proceedings in separate article of the procedural code.Conclusons. The absence of an independent system of administrative procedural principles confirms the thesis that administrative proceedings cannot be considered an independent branch of law separated from civil proceedings law. However, the priority of immediate execution of a court decision is a characteristic feature (perhaps even a principle) of administrative proceedings.